The quantum nature of light : from photon states to quantum fluids of light - Mendonça, J. T. (José Tito) (IOP (Series). Release 22., 2022)
This book provides an overview of quantum light phenomena and extends the traditional Quantum Optics, to include quantum fluids of light and the complete electromagnetic vacuum. The first part of the book includes basic electromagnetic field quantisation, the characterisation of quantum photon states and elementary photon-atom interactions. Secondly, quantum fluids of light are explored such as recent areas as Bose-Einstein condensation, light vortices and superfluid light. Finally, the last section of the book focusses on a more complete description of quantum vacuum, which includes electron-positron states. The book is intended to make the bridge between these three somewhat distinct aspects of the quantum states of light. The main audiences for the book include researchers and advanced students in quantum technology including quantum optics, metrology and computing. Part of IOP Series in Quantum Technology.